The eternal criminal record - Jacobs, James B. (Harvard University Press, 2015)
Intelligence and investigative databases -- Linking bodies to criminal histories -- Court records -- Privatizing criminal records -- Whether to create a criminal record -- Sealing, purging, and amending conviction records -- Erroneous records problems -- Transparency of criminal convictions -- Public access to arrestee information -- Publicly accessible criminal records and punishment theory -- Criminal justice consequences of a criminal record -- Second class citizens by law -- Employment discrimination based upon criminal record